Yield Interactions of Wheat Genotypes to Dates of Seeding in Eastern Mid Hills of Nepal - Bhattarai, Rudra; Chaudhary, Bedanand; Thapa, Dhruba Bahadur; Puri, Ramesh Raj; Chaudhary, Ram Nath; Sapkota, Bibek; Baral, Kiran; Shrestha, Shukra Raj; Adhikari, Surya Prasad (Journal of Nepal Agricultural Research Council, 2016)
Wheat (Triticum aestivum L.) is one of the major cereal crops and staple food sources in Nepal. Wheat varieties being popular in mid hill regions are still in the early stages of adoption. Identification of appropriate date of seeding plays important role in enhancing the adoption rate ensuring the sustainable production. Therefore, three dates viz 15th November, 1st and 15th December for seeding and twenty eight wheat genotypes were evaluated in a split plot design with two replications for two consecutive seasons in 2011/12 and 2012/13 at an altitude of 2200 masl of eastern Nepal. The results showed genetic differences and interaction effect of genotypes with the dates of sowing on grain yield, panicle length and effective tillers per square meter. The wheat sown on 1st December showed the highest yield as compared to other sown dates. Similarly, WK1907, WK1911, WK1803, WK1915, WK1909, WK1714 and WK1803 produced highest yield among the tested genotypes with retaining maximum number of effective tillers and posed suitable maturity across all sowing date. Journal of Nepal Agricultural Research Council Vol.1 2015 pp.33-36